Man pinning a corsage on a woman - Unknown:::Creator::::::::::::
Negative shows a young man in a uniform pinning a corsage on an young woman. She is wearing a skirt and a top with lace and a bow. Her hair is styled up on her head and she is holding a clutch purse.